An analysis of survey measurements of tsetse challenge to trypanotolerant cattle in relation to aspects of analytical models of trypanosomiasis - Rawlings, P.; Dwinger, R.H.; Snow, W.F. (Cambridge University Press, 1991)
The recent development of analytical models of trypanosomiasis has increased the general applicability of models to the strategic control of the disease. An analysis of detailed data on tsetse abundance and infection rates and trypanosome prevalence in village-based trypanotolerant cattle over 4 years in The Gambia showed that seasonal patterns of abundance in Glossina morsitans-infested areas were consistent, and that the rates of trypanosome infection remained relatively unchanging. However, there were two distinct seasonal trypanosome prevalence patterns in cattle, with peaks occurring either in May/June/July or November/December. The peaks of trypanosome prevalence therefore occurred either 4 months before or after the times of peak challenge from G. morsitans, not 1 or 2 months after as predicted by analytical models. In G. palpalis-infested areas there was little seasonal variation in abundance or trypanosome infections, but peak trypanosome prevalence still occurred mostly in June/July. Despite the incongruity between the months of peak prevalence and challenge, the overall annual prevalence rates and tsetse challenge indices showed a significant linear relationship. It is concluded that existing analytical models need to be refined to take into account trypanotolerance and the various influences on the expression of this trait.